2020
DOI: 10.3390/healthcare8040485
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dental Malocclusion on Body Posture and Foot Posture in Children: A Cross-Sectional Study

Abstract: The number of studies that investigate the correlations between the temporomandibular system and body posture, postural control, or the distribution of plantar pressure has recently been increasing. However, most of the existing information is not conclusive. Therefore, the study objective was to evaluate if the features of dental malocclusion are correlated with body posture alterations at the lower limb level. This is a multicentre cross-sectional study with 289 children (8–14 years). Angle’s molar relation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Cabrera-Domínguez et al (2021) and Pérez-Belloso et al (2020) found statistically significant differences between the foot contact area and the CoG of a human body in different occlusal classes. They noted a forward shift of the CoG in Angle Class II patients and a backward shift of the CoP in Angle Class I and III patients [ 10 , 12 ]. The results of this study are consistent with the above-mentioned observations [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cabrera-Domínguez et al (2021) and Pérez-Belloso et al (2020) found statistically significant differences between the foot contact area and the CoG of a human body in different occlusal classes. They noted a forward shift of the CoG in Angle Class II patients and a backward shift of the CoP in Angle Class I and III patients [ 10 , 12 ]. The results of this study are consistent with the above-mentioned observations [ 10 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…They noted a forward shift of the CoG in Angle Class II patients and a backward shift of the CoP in Angle Class I and III patients [ 10 , 12 ]. The results of this study are consistent with the above-mentioned observations [ 10 , 12 ]. This study also found that Angle Class II patients had their body CoG significantly more often shifted forward, while those diagnosed with Angle Class I and III had it shifted backward ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People with TMD are 5.5 times more likely to develop diseases of other joints than people without disorders [67]. In opposition to these studies, Perez-Belloso did not find a direct relationship between the masticatory system and the lower limb [68].…”
Section: Methodsmentioning
confidence: 78%
“…Pérez-Belloso et al did not found a direct relationship between the stomatognathic system and the structures of the lower limb (hip, knee, and foot) even if a strong correlation between dental malocclusion and the position of the baricentre emerged 13 .…”
Section: Introductionmentioning
confidence: 94%